Comparison of the Effectiveness of Cognitive Behavioral Therapy and Schema Therapy on Perseverative Thinking in Young Adults with Depressive Symptoms - Rahemi Nooran, Shily; Tizdast, Taher; Nasrolahi, Bita (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2026)
Objective: The present study aimed to compare the effectiveness of Cognitive Behavioral Therapy and Schema Therapy on reducing perseverative thinking in young adults with depressive symptoms. Methods and Materials: This applied study employed a quasi-experimental design with a pretest–posttest control group and a two-month follow-up. The statistical population consisted of young adults with depressive symptoms who referred to counseling and psychological clinics in District 1 of Tehran between December 2024 and June 2025. From this population, 45 participants who met inclusion criteria were selected using purposive sampling and randomly assigned to three groups: Cognitive Behavioral Therapy (n = 15), Schema Therapy (n = 15), and control (n = 15). The experimental groups received eight structured group sessions based on established CBT and Schema Therapy protocols, while the control group received no intervention during the study period. Perseverative thinking was assessed at pretest, posttest, and follow-up using the Perseverative Thinking Questionnaire. Data were analyzed using descriptive statistics, mixed-design repeated measures ANOVA, multivariate analysis of variance, and Bonferroni post hoc tests in SPSS software. Findings: Repeated measures analysis indicated no significant main effect of group; however, the main effect of time was statistically significant, demonstrating overall changes in perseverative thinking across measurement points. Importantly, the interaction effect between time and group was statistically significant, indicating differential patterns of change among groups. Bonferroni post hoc comparisons revealed that Schema Therapy produced a significant reduction in perseverative thinking compared to the control group at posttest, whereas Cognitive Behavioral Therapy did not significantly differ from the control group. Within-group analyses showed that Schema Therapy led to significant reductions from pretest to posttest and from pretest to follow-up, with maintained effects over time, while no significant changes were observed in the CBT and control groups. Conclusion: The findings suggest that Schema Therapy is more effective than Cognitive Behavioral Therapy in reducing perseverative thinking among young adults with depressive symptoms, with effects sustained over a two-month follow-up period.